The Economic Costs and Benefits of Investments in Municipal Water and Sanitation Infrastructure: A Global Perspective - Dale Whittington W. M. Hanemann (CUDARE Working Papers, 2006)
This paper presents illustrative estimates of the costs and benefits of investments in municipal water and sanitation systems in developing countries. Four sources of information on the economic benefits households receive from improved municipal water and sanitation services are reviewed: (1) prices charged for vended water, (2) avertive expenditures, (3) avoided costs of illness, and (4) stated preference studies. There is little evidence to suggest that the current monthly benefits of improved water and sanitation services exceed the monthly costs. The most important limitation of such comparisons of annual costs and benefits is that benefits per household may well grow over the life of the investments, but this possibility does not ensure that such projects will pass a cost-benefit test.